Predictors of participation in preventive health examinations in Austria - Sophie Brunner‐Ziegler; Anita Rieder; K. Viktoria Stein; Renate Koppensteiner; Kathryn Hoffmann; Thomas E. Dorner (2013)
Preventive health check-ups in Austria are offered free of charge to all insured adults (98% of the population) and focus on early detection of chronic diseases, primary prevention, and health counseling. The study aims to explore predictors of compliance with the recommended interval of preventive health check-up performance.Source of data was the Austrian Health Interview Survey 2006/07 (15,474 subjects). Participation in a preventive health examination during the last three years was used as dependent variable. Socio-demographic and health-related characteristics were used as independent variables in a multivariate logistic regression analysis.Results show that 41.6% of men and 41.8% of women had attended a preventive health check-up within the last three years. In multivariate analysis, subjects ≥ 40 years, with higher education, higher income or born in Austria were significantly more likely to attend a preventive health check-up. Furthermore, a chronic disease was associated with a higher attendance rate (OR: 1.21; CI: 1.07-1.36 in men; OR: 1.19; CI: 1.06-1.33 in women).Attendance rates for health check-ups in the general Austrian population are comparatively high but not equally distributed among subgroups. Health check-ups must increase among people at a young age, with a lower socio-economic status, migration background and in good health.